KORELASI ANTARA PERIODE KRITIS DAN PEMEROLEHAN BAHASA - Putri, Tia Aprilianti (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
Critical period is the period in which a human being is very sensitive to environmental stimuli, usually it occurs from the very beginning humans were born until they are puberty. This critical period is closely related to humans’ language acquisition. However, if during this period humans did not get the stimulus to learn language well, then their ability to acquire the language would be difficult, or even fail. The purpose of this study was to prove whether there was a correlation between the critical period hypothesis initiated by Eric H. Lenneberg with humans' language acquisition. The research method used in this study was to compare 3 case samples that occurred in Genie, Victor, and Isabella. All of them experienced language delay at first, but after getting treatment they showed different results. Genie and Victor did not show significant language development, whereas in the case of Isabelle, her language acquisition showed very good results. The difference result of that experimental because of their age difference. Therefore, it can be said that there is a correlation between a critical period and one's language ability.